Manias, Panics and Crashes A History of Financial Crises - Kindleberger, Charles Poor 1910-2003; Aliber, Robert Z. 1930- (Palgrave Macmillan UK, 2005)
Manias, Panics and Crashes , is a scholarly and entertaining account of the way that mismanagement of money and credit has led to financial explosions over the centuries. Covering such topics as the history and anatomy of crises, speculative manias, and the lender of last resort, this book has been hailed as 'a true classic...both timely and timeless.' In this new, updated fifth edition, Kindleberger and Aliber expand upon the ideas presented in the previous edition, and include two new chapters on the real estate price bubble that occurred in Norway, Sweden and Finland at the end of the 1980s, and the three asset price bubbles that occurred between 1985 and 2000 in Japan and other Asian countries. Selected as one of the best investment books of all time by the Financial Times, Manias, Panics and Crashes puts the turbulence of the financial world in perspective